Exploring co-production of falls management approaches in care home settings - Hallam-Bowles, Frances (2025)
Background Co-production is a collaborative approach where stakeholders from different groups or backgrounds share power and work together as equals in their views and participation throughout all research stages. Care home residents and staff are underrepresented in past research. Using co-production approaches may be beneficial in care home settings to democratise knowledge and develop implementation approaches to address complex problems. Co-production aligns with health and social care policies which advocate for integrated care to enhance the support available to care home residents. However, co-production in care homes is challenging and there is a lack of context-specific guidance to support authentic co-production in these settings. This PhD study explored how resident falls are managed in care homes as a case study to learn about using co-production approaches in care home settings and to develop recommendations for future research. Methods Three workstreams were undertaken to explore how co-production approaches can be applied in care home settings to develop and implement falls management approaches. A scoping review was undertaken in workstream 1 (WS1) to map co-production approaches used in care homes in previous research. Observations and interviews with staff, residents and health and social care (HSC) leaders explored organisational and contextual factors influencing co-production of falls management in care homes in workstream 2 (WS2). A qualitative evaluation using observations and reflection meetings was completed in workstream 3 (WS3) to evaluate how co-production occurred when developing a novel model for implementing falls management in care homes. All workstreams were underpinned by the National Institute for Health and Care Research (NIHR) principles of co-production as a core conceptual framework. Findings were mapped across workstreams and recommendations were produced to improve future co-production approaches in research with care homes. Patient and public involvement and engagement was embedded throughout all stages of the research. Findings WS1 identified limited use of co-production approaches in past care home research. Most studies used qualitative and participatory approaches. Evaluation of co-production processes and outputs was highlighted as a research gap. WS2 highlighted that co-production of falls management approaches involved many stakeholders with different organisational practices and collaboration was negatively affected by complex care home systems. Authentic co-production in line with the NIHR principles was partially achieved when developing a model for falls management in WS3 and led to reported benefits, such as improved confidence. The findings of this research elucidate that co-production in care homes is a complex process influenced by many factors. Characteristics of individuals (for instance confidence, roles, impairments) and interpersonal relationships affected participation in co-production in this setting. Pressures and priorities affecting care homes and wider HSC organisations across the system had implications for collaboration. Creating safe spaces for care home staff and residents to challenge dominant voices and using a flexible approach were identified as key facilitators of co-production. The findings highlight that co-production conflicts with the existing culture of participating care homes, and HSC and research organisations, leading to discomfort for participating stakeholders. Adequate time and resources are required to overcome potential challenges. Conclusion Sixteen recommendations are provided to support authentic co-production approaches in line with the NIHR principles for future care home research. These recommendations are now ready for implementation and evaluation and should be considered when planning and conducting co-production activities in care homes.